Management And Reporting Of Financial Reports Through The Village Financial System Application (SISKEUDES) - Tita Kartika (Journal of Business, Accounting and Finance, 2022)
Siskeudes is one form of government improvement in managing financial reports and village fund accountability. The benefits of siskeudes for the village are that it can manage village finances to be more transparent and accountable. The problem in this reseach is how is village financial management based on the Village Financial System (Siskeudes) application in Desa Ciptasari Kabuaten Sumedang, what is the procedure for reporting village finances based on Village Financial System (Siskeudes) application in Desa Ciptasari Kabupaten Sumedang, what are the obstacles to implementing the Village Finance Application (Siskeudes) in Desa Ciptasari Kabupaten Sumedang. The research method used is descriptive qualitative method. The data collection techniques used in this study were the observation method, the interview method and the library study method. The results of reseach conducted Desa Ciptasari Kabupaten Sumedang that in its application the siskeudes application is able to create accountable financial reports and can reduce the occurrence of corruption. However, this application also poses several obstacles, including account codes and activity menus that are not yet available and the internet network is slow.